EFFECTS OF TRANSITION FROM SUPERVISED CARDIAC REHABILITATION PROGRAM TO UNSUPERVISED IN INDIVIDUALS WITH HEART DISEASES - Palma, Mariana Romanholi; Freire, Ana Paula Coelho Figueira; Rossi, Melissa De Carvalho; Abegão, Mickeline Fidalgo; Vanderlei, Luiz Carlos Marques; Pacagnelli, Francis Lopes (Universidade Estadual de Maringá, 2016)
ABSTRACT Many post-surgical patients after coronary artery bypass who are eligible for cardiac rehabilitation are not being attended. Progression in the centers which deliver the rehabilitation is important, so that others may benefit from treatment. The objective of this study was to investigate the possible effects of transition froma program of supervised cardiac rehabilitation (Phase III) to unsupervised (Phase IV), for two months, on functional capacity, heart rate variability (HRV) and cardiometabolic parameters of individuals with a diagnosis of cardiovascular disease. In total, 10 individuals were evaluated,who had been on the Phase III cardiac rehabilitation program for at least six months and who were eligible for unsupervised rehabilitation. The parameters analyzed were functional capacity, HRV, blood pressure, blood glucose, waist-hip ratio and body mass index. Individuals undergoing unsupervised activities for two months presented no significant changes in the evaluated parameters. The cardiovascular and functional adaptations achieved in Phase III were maintained in Phase IV and should be encouraged for individuals at low cardiovascular risk who demonstrated benefits in Phase III.

RESUMO Muitos pacientes pós-cirúrgicos de revascularização do miocárdio elegíveis para reabilitação cardíaca não estão sendo atendidos, é importante uma rotatividade nos centros de atendimento, de forma que outros possam se beneficiar do tratamento. O objetivo deste estudo foi investigar possíveis efeitos da transição de programa de reabilitação cardiovascular supervisionado (fase III) para não supervisionado (fase IV), durante dois meses, na capacidade funcional, variabilidade da frequência cardíaca (VFC) e parámetros cardiometabólicos de individuos com diagnóstico de doenças cardiovasculares. Foram avaliados 10 indivíduos que encontravam-se em programa de reabilitação cardíaca fase III por período mínimo de seis meses, elegíveis para reabilitação não supervisionada. Os parámetros analisados foram capacidade funcional, VFC, pressão arterial, glicemia capilar, relação cintura quadril e índice de massa corpórea. Indivíduos submetidos a atividades não supervisionadas durante dois meses, não apresentaram alterações significativas nos parámetros avaliados. A Fase IV manteve adaptações obtidas e deve ser incentivada à indivíduos de baixo risco cardiovascular que apresentaram beneficios na fase III.
EFEITOS DA TRANSIÇÃO DE UM PROGRAMA DE REABILITAÇÃO CARDÍACA SUPERVISIONADO PARA NÃO SUPERVISIONADO EM INDIVÍDUOS COM CARDIOPATIAS
Keywords: Cardiovascular diseases; Physical education and training; Physical therapy speciality; Doenças cardiovasculares; Educação Física e treinamento; Fisioterapia